Narrative Review on Dental Porcelain and Ceramics: A New Classification - Osamah Alsulimani (Asian Journal of Pharmaceutics (AJP), 2025)
In recent years, there has been a surge in the development and introduction of various ceramic materials in restorative dentistry. It has become increasingly evident that there is growing interest in ceramic materials in dentistry. These materials are preferred over traditional ones because of their superior esthetic qualities and ability to meet patients’ demands for improved appearance. The advent of computerized systems for producing dental restorations and the development of novel microstructures for ceramic materials have significantly changed the clinical workflow for dentists and technicians. This has led to new treatment options being available to patients. This review includes a comprehensive search of literature and clinical survival papers on ceramic materials in dentistry published between the 1960s and 2024. Major databases, such as PubMed, Scopus, and Google Scholar, were used for the investigation. The aim is to summarize the literature and update clinicians’ knowledge about dental ceramics and their clinical applications. This review suggests a new classification of dental ceramics based on their composition, considering commercially available materials. A summary of each category’s mechanical properties and clinical applications is also provided. The purpose is to simplify the understanding of dental ceramics and assist clinicians in choosing appropriate materials for their patients.